Optimisation of rhamnolipids produced by Pseudomonas aeruginosa 181 using Response Surface Modeling - Al-Araji, Laith Issa Yassin; Raja Abd Rahman, Raja Noor Zaliha; Basri, Mahiran; Salleh, Abu Bakar (Springer Berlin / Heidelberg, 2007)
This work investigated the optimisation of the fermented culture medium for maximisation of rhamnolipids production produced by Pseudomonas aeruginosa 181 using Response Surface Modeling (RSM). A two full factorial central composite experimental design was used in the design of experiments and in the analysis of results. This procedure limited the number of actual experiments performed while allowing for possible interactions between the parameters (pH, stirring rate, casamino acid concentration and incubation period) on the production of biosurfactants. Production carried out at larger volumes of one litre using Bioreactor under RSM-optimised conditions yielded 3.61 g l−1 of products after purification by acid precipitation.